1992
DOI: 10.1109/16.158793
|View full text |Cite
|
Sign up to set email alerts
|

CW measurement of HBT thermal resistance

Abstract: istics and simulation results of the SiGe HBTs. The extracted value of R th using our method is 500.7 K/W and the extracted value from the two-temperature method is about 500 K/W. We also compared the results taken from pulsed I-V measurements with 1% duty circle of pulsed V BE . Excellent agreement is still obtained. In Figure 5, the extracted values of R th show good agreement compared to the results taken from the isothermal measurements [8]. The RMS error obtained is less than 0.35%. CONCLUSIONA simple and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(73 citation statements)
references
References 4 publications
5
68
0
Order By: Relevance
“…2 This relationship can be linear as in [2], or almost linear (within 10% of a straight line) as in [3]. However, and , can be assumed to be univocal functions of only.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 This relationship can be linear as in [2], or almost linear (within 10% of a straight line) as in [3]. However, and , can be assumed to be univocal functions of only.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Moreover, it can be demonstrated that if one assumes a dependence on the output power for , such as (6) the relative error in the junction temperature of points A and C in Fig. 1, having the same (but a different ) is given by (7) 3 Neglecting the dc power dissipated at the base. Also the RF input power has been neglected as the power gain is normally quite high in HBTs.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third factor is to note that the current bias and junction temperature are not totally independent since junction temperature is a function of current injection. Methods and techniques for estimating junction temperatures of HBTs under current/voltage biases are discussed elsewhere [12][13][14][15][16] and are not the subject of this paper.…”
Section: Hbt Device Reliabilitymentioning
confidence: 99%
“…The extraction method is based on DC measurements only, and can be considered as an improved CB variant of the classic approach proposed by Dawson et al [10]. The procedure is articulated in two steps, namely, (1) the calibration of the temperature coefficient of the base-emitter voltage, which is …”
Section: Thermal Resistance Extraction Approachmentioning
confidence: 99%